Pseudomonas aeruginosa in public water supply - Anversa, Laís; Stancari, Regina Célia Arantes; Garbelotti, Maricene; Ruiz, Luciana da Silva; Pereira, Virgínia Bodelão Richini; Nascentes, Gabriel Antonio Nogueira; Dantas, Stéfani Thais Alves [UNESP]; Rall, Vera Lúcia Mores [UNESP] (IWA Publishing, 2019)
Water is indispensable for life and its quality is directly related to public health. The objective of this study was to investigate the presence of Pseudomonas aeruginosa in public water supply in municipalities in São Paulo State, Brazil. Analyses were carried out at the Adolfo Lutz Institute between February and December 2016, and included physicochemical (chlorine, pH, color, turbidity and nitrate), and microbiological parameters (total coliforms and Escherichia coli), as well as P. aeruginosa, with susceptibility tests to antimicrobial agents and biofilm production capacity by the strains isolated. In total, 251 water samples were evaluated and 19 (7.6%) presented P. aeruginosa. No significant differences were observed between the physicochemical parameters found in the positive and negative samples for this bacterium, but the samples containing total coliforms were also those with the highest positivity for P. aeruginosa. All samples with P. aeruginosa reported chlorine concentrations between 0.2 and 2.0 mg/L, as required by Brazilian legislation, demonstrating this bacterium’s resistance to conventional water treatment processes. Although not resistant to the antimicrobials tested, most strains isolated were classified as strong biofilm producers, emphasizing the need for further studies involving water supply quality.
Keywords: Biofilm; Pseudomonas aeruginosa; Public health; Water; Water supply